WATERFLOODING OPTIMIZATION IN CARBONATE RESERVOIR AT FIELD X USING RESERVOIR SIMULATION - Novia Fazilani; Sugiatmo Kasmungin (Lembaga Penelitian Universitas Trisakti, 2017)
Field X consist of a carbonate reservoir, producing since April 2014 with only 2existing wells present, which is well NF-01 and NF-02. Production history of the field wasperformed from year 2014 until 2016. The original oil in place of Field X is 9.204 MMSTB(volumetric) and 9.0308 MMSTB (simulation). In this study, the software used for thedevelopment of Field ‘X’ is Computer Modeling Group (CMG) IMEX Black Oil, by applyingwaterflooding as a method of optimizing the field. All the data up until history matchingwas given and the focus of this final assignment is to evaluate and predict severalscenarios. The period of development is done for 19 years which is until December 2035.Several scenarios predicted were In-fill, conversion of wells, peripheral, 5-spot patternsand pilot studies. The injection rates of each scenarios are 500-2000 bwpd where it isanalzyed to see if there were significant changes effected from each of the injection rates.As the optimisation were conducted, recovery from each injection rates varies. Aftercarrying out the simulation the implementation of waterflood was insignificant. Theoptimum scenario from waterflooding implementation is the peripheral pattern of 38.17%.